2020
DOI: 10.33371/ijoc.v14i4.738
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis in Children with Acute Lymphoblastic Leukemia

Abstract: Background: Sepsis is the leading cause of morbidity and mortality in children worldwide, with around 75,000 inpatients each year and nearly 50% dying in pediatric hospitals. Acute lymphoblastic leukemia (ALL) in childhood is a malignancy originating from lymphoid progenitor cells, usually at the age of 2–6 years. Children with ALL contribute 30% to childhood cancer cases under 15 years old. Sepsis in pediatric patients increases mortality significantly. A previous study showed that the prevalence of sepsis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…ALL accounts for 25% of cancer diagnoses in children and the peak incidence occurs at the age of 2-5 years (16,17). Aisyi et al (18) reported that 94 ALL children at Dharmais Hospital from January 2016 to December 2018 was male sex, with percentage of 60.6%, with a median age of 5 (1-8) years. Kakaje et al (19) reported that the highest incidence of ALL occurred at the age of 5-9 years.…”
Section: Discussionmentioning
confidence: 99%
“…ALL accounts for 25% of cancer diagnoses in children and the peak incidence occurs at the age of 2-5 years (16,17). Aisyi et al (18) reported that 94 ALL children at Dharmais Hospital from January 2016 to December 2018 was male sex, with percentage of 60.6%, with a median age of 5 (1-8) years. Kakaje et al (19) reported that the highest incidence of ALL occurred at the age of 5-9 years.…”
Section: Discussionmentioning
confidence: 99%